Drinking water quality and antibiotic resistance of E. coli and Salmonella spp. from different sources in Gweru urban, Zimbabwe - Mugadza, Desmond Tichaona; Nduku, Sibusisiwe Isabel; Gweme, Edlyn; Manhokwe, Sherpherd; Marume, Patience; Mugari, Amiel; Magogo, Charles; Jombo, Talknice Zvamaziva (Springer, 2022)
The study focused on assessing drinking water quality from different sources in Gweru urban. Seventy six samples were collected from 6 different locations and analysed for physicochemical parameters and microbial quality. Bacteria isolates were identified using matrix-assisted laser desorption ionization-time of flight mass spectrometry and antibiotic susceptibility was determined for 4 isolates that had been identified as Escherichia coli (2) and Salmonella spp. (2). Although most samples were within World Health Organisation limits for most parameters, none met coliform limits. pH ranged between 6.2 and 6.9. Salmonella prevalence was 2%. Escherichia coli and Salmonella spp. isolates were resistant to at least three antibiotics. The study showed inconsistent water quality across the city and contamination in alternative water sources.